A positivação da Bioética na OMC: um debate entre o protecionismo técnico e as práticas desleais de comércio - Menezes, Rosangela Cunha de (2015)
The World Trade Organization (WTO) some major problems brought to the Dispute Settlement Body (DSB) come from conflicts involving biolaw themes. There are, it seems, conflicting interests between developed and developing States. One of the main causes of these disputes is the raising of technical and ecological barriers that limit the multilateral trade. Thus, this work has the scope to analyze the historical bases, conceptual and legal of Biolaw and Bioethics, setting up as a technical barrier to relations of International Trade and verify the use of Biolaw as barriers to multilateral trade, WTO and finally verify the application of the principles of Biolaw and international environmental law and the courts of the Dispute Settlement Body of the World Trade Organization.